Three new species of Cyana Walker, 1854 from Indochina and China (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2019)
Three new species of the genus Cyana Walker, 1854 are described: C. artemis sp. n. (southeastern China, Thailand, Laos, Vietnam), C. butyracea sp. n. (Vietnam) and C. kucheri sp. n. (Vietnam). The first two species are related to the Himalayan C. moelleri (Elwes, 1890) and the Indochinese C. intercomma Černý, 2009. Despite the external similarity of C. kucheri sp. n. to C. moelleri and its allies, by the genitalia structure this species is related to C. gazella (Moore, 1872). Adults and male and female genitalia of new and related species are illustrated.